Political and Legal Dimension of the Implementation of the Tapera Program in the Protection of Private Workers' Rights: A Study in Urban Areas - Iskandar, Iskandar; Lesmana Putra, Ryan Fachryan; Sudrajat, Shinta Azzahra (Fakultas Hukum Universitas Sultan Ageng Tirtayasa, 2024)
The People's Housing Savings Program (Tapera) is a solution for people's welfare provided by the government with the aim of helping financial welfare related to decent housing. Law Number 4 of 2016 concerning People's Housing Savings (Tapera Law) is present as a legal basis for the community, especially private workers who have the right to have decent and affordable housing, where the government and other parties will be bound. However, problems occur when the Government sets a contribution of 2.5% which is deducted every month from workers' salaries. This study aims to regulate the management of Tapera funds in an accountable and professional manner to realize transparency in every management of funds collected from the community to be used for the purposes that have been set. The research method used is empirical research, with a statute approach, a conceptual approach and a sociological approach to law. Data sources are obtained from primary, secondary, and tertiary legal materials, which are collected through interview techniques, documentation, and decisions. Then, the data is analyzed prescriptively. The results of this study show that long-term welfare is not owned by private workers, because the impact of the reduction in obtaining decent and affordable housing creates an unstable financial impact.